2016
DOI: 10.1177/0272431615626301
|View full text |Cite
|
Sign up to set email alerts
|

The Trajectory of Popularity Goal During the Transition to Middle School

Abstract: The trajectory of early adolescents' popularity goal during the transition to middle school was examined in a diverse sample of 401 students. Popularity goal was assessed at five time points from the spring semester of fifth grade through the spring semester of seventh grade with the transition to middle school occurring between the fifth and sixth grades. Results showed a significant increase in youth's endorsement of popularity goal after the transition to middle school followed by a significant decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 71 publications
(133 reference statements)
0
44
1
Order By: Relevance
“…A. P. Del Prette, 2009). The presentation of these behaviors is necessary for the emergence of healthy interpersonal relationships in adolescence, since adolescents are more susceptible to yielding to the negative pressure and influence of their peers, favoring the emergence of behavioral problems (Dawes & Xie, 2016;Eccles & Roeser, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A. P. Del Prette, 2009). The presentation of these behaviors is necessary for the emergence of healthy interpersonal relationships in adolescence, since adolescents are more susceptible to yielding to the negative pressure and influence of their peers, favoring the emergence of behavioral problems (Dawes & Xie, 2016;Eccles & Roeser, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, the socalled Middle School is currently divided into Initial Years, which comprise 1st to 5th grade (equivalent to Elementary School), and Final Years, which comprise the 6th to 9th grades (equivalent to Middle School). The admission in the 1st grade (Cadima, McWilliam, & Leal, 2010), as well as in 6th grade are two important transitions experienced by students in MS (Dawes & Xie, 2016;Lane et al, 2015). However, despite growing publications about the transition to the 1st grade, little attention has been given to the transitions occurring within the same school segment, as is the case of the passage from the 5th to the 6th grade (Lane et al, 2015).…”
Section: Influencia De Las Habilidades Sociales Y Factores De Estrés mentioning
confidence: 99%
See 1 more Smart Citation
“…However, not everyone strives for this limited resource to the same extent, as youth differ in how much they value high status, such as being popular. It seems that adolescents who are more popular than their peers are the ones who tend to be more motivated to remain or become even more popular, as previous studies have found a moderate association between actual popularity and popularity goal (e.g., Dawes and Xie 2017). As such, high-status youth who have experienced the benefits of popularity (e.g., resources, attention : Hawley 1999: Hawley , 2003) may subsequently have a higher popularity goal.…”
Section: Popularity and Popularity Goalmentioning
confidence: 90%
“…A peer nomination procedure was used (see Farmer, Estell, Bishop, O'Neal, & Cairns, ; Farmer & Rodkin, ; Rodkin, Farmer, Pearl, & Van Acker, ). To measure perceived popularity, each participant was asked during the group survey session to nominate from free recall classmates who best fit the descriptor ‘popular’ (‘This person is popular at school, many classmates like to play with them or do things with them’) which has been shown to measure perceived popularity (Dawes & Xie, ; Shi & Xie, ). The participants were also asked to nominate peers who best fit the descriptor ‘coolness’ (‘This person is really cool.…”
Section: Methodsmentioning
confidence: 99%